The Effect OfDifferent Surface Area of the Aquarium andStocking Density On Growth and Survival Rate of Siammese Catfish Larvae (Pangasius hypophthalmus) - Arvina Vindi Nina; Hamdan Alawi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThe aim of this research was to determine the effect of different surface area of the aquarium and stocking densityon growth and survival rate of siammese catfishlarvae reared with a water recirculation system. This research was conducted from October-December 2019 at the Fish Hatchery and Breeding Laboratory, Fisheries and Marine, University of Riau. The Method used was a Factorial Completely RandomizedDesign with two factors.The first was surface area of aquarium with three levels, namely 30x30x30 cm3 (Lp1), 30x40x30 cm3 (Lp2) and 30x50x30 cm3(Lp3). While the second factor was stoking density with three levels namely 250 larvae/m2 (Pt1), 500 larvae/m2, 1000 larvae/m2. The larvae were reared in 15 L aquarium for 40 days. The result showed that surface area and stocking density gave a significant effect in absolute weight, absolute length, specific growth rate and survival rateof siammese catfish larvae reared in 40 day. Surface area of 30x40x30 cm3 and stocked at density of 250 larvae/m2 were signifycanthy the highest in absolute weight (7,73 gr), absolute length (4,63 cm), spesific growth rate (5,35 %/day) and survival rate (90,00 %). The water quality parameters during research were rangedtemperature26,4-27,5°C, pH 5,2-6,2 and dissolved oxygen 3,6-4,67mg/l. Keywords : Surface area, Stocking denstity,Siammese Catfish Larvae,Growth and Survival rate